Riverfront development case study: Kuantan river / Siti Zaleha Muhamad - Muhamad, Siti Zaleha (Faculty of Architecture, Planning and Surveying, 2010)
As we know, water is related to the river. River is one of the important sources to people in the world. The development also is very important for the improvement of certain areas. Some of the areas have not enough space for the development because the area is covered with water and not land such as in Pahang. Pahang have the longest distance of river than other states. The riverfront development is one of the actions that had been taken by authority to fulfill the requirement of the development for that area. In this study, it is an investigation about the riverfront development surrounding Kuantan River. The investigation is more about the guideline concepts and problems that occurred to the riverfront development at Kuantan River. The guidelines concept that had been used by all parties related to the development such as the authority and the developers. The guidelines concept that had been used by them is more to the condition and limitation for the development that had been developed. When riverfronts development started in the areas, the problems and issues will arise especially the ones involving society surrounding. The problem occurred involve the aspect of physical, economic and social. Although some riverfront development projects continue to remain profitable with successfully maintaining the public access component and many have not. This research project will show the implementation of guidelines concept and problem that occurred related to the riverfront development at Kuantan River.